Optimal intensity measures for the structural assessment of buried steel natural gas pipelines due to seismically-induced axial compression at geotechnical discontinuities. Issue 131 (April 2020) - Tsinidis, Grigorios; Di Sarno, Luigi; Sextos, Anastasios; Furtner, Peter
Abstract: This paper investigates the efficiency and sufficiency of various seismic intensity measures for the structural assessment of buried steel natural gas (NG) pipelines subjected to axial compression caused by transient seismic ground deformations. The study focuses on buried NG pipelines crossing perpendicularly a vertical geotechnical discontinuity with an abrupt change on the soil properties, where the potential of high compression strain is expected to be increased under seismic wave propagation. A detailed analytical framework is developed for this purpose, which includes a 3D finite element model of the pipe-trench system, to evaluate rigorously the pipe-soil interaction phenomena, and 1D soil response analyses that are employed to determine critical ground deformation patterns at the geotechnical discontinuity, caused by seismic wave propagation. A comprehensive numerical parametric study is conducted by employing the analytical methodology in a number of soil-pipeline configurations, considering salient parameters that control the axial response of buried steel NG pipelines, i.e. diameter, wall thickness and internal pressure of the pipeline, wall imperfections of the pipeline, soil properties and backfill compaction level and friction characteristics of the backfill-pipe interface. Using the peak compression strain of the pipeline as engineering demand parameter and a number of regression analyses relative to the examined seismic intensity measures, it is shown that the peak ground velocity PGV at ground surface constitutes the optimum intensity measure for the structural assessment of the examined infrastructure. Highlights: The efficiency and sufficiency of seismic intensity measures for buried NG pipelines is tested. Particular emphasis is placed on axially compressed buried pipelines crossing geotechnical discontinuities. Optimal seismic intensity measures are proposed for the assessment of NG pipelines.